2019
DOI: 10.1002/brb3.1429
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte/lymphocyte ratio is associated with carotid stenosis in ischemic stroke: A retrospective analysis

Abstract: Background Carotid artery stenosis, mainly caused by carotid atherosclerosis, is related to ischemic stroke. This study was to investigate whether monocyte/lymphocyte ratio (MLR) was associated with increased severity of carotid stenosis in patients with ischemic stroke. Methods A total of 395 participants with ischemic stroke were retrospectively analyzed. The severity of carotid stenosis was evaluated by ultrasound examination. Patients were divided into two groups: nonsevere stenosis group and severe stenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…In another study, Ahbap et al observed higher NLR among dipper versus non dipper hypertensives with CKD supporting our results. The MLR is rapidly emerging as another important marker of vascular inflammation has been linked to carotid stenosis severity in ischaemic stroke and to the severity of coronary disease and cardiovascular mortality [28][29][30]. There was no association between PLR and either blood pressure dipping status or MACE in our cohort.…”
Section: Discussionmentioning
confidence: 57%
“…In another study, Ahbap et al observed higher NLR among dipper versus non dipper hypertensives with CKD supporting our results. The MLR is rapidly emerging as another important marker of vascular inflammation has been linked to carotid stenosis severity in ischaemic stroke and to the severity of coronary disease and cardiovascular mortality [28][29][30]. There was no association between PLR and either blood pressure dipping status or MACE in our cohort.…”
Section: Discussionmentioning
confidence: 57%
“…And those cutoffs are 0.24 in men and 0.20 in women. In other researches on the predictive capability of MLR, an optimal cutoff point for predicting carotid artery stenosis in ischemic stroke population is 0.20 ( 13 ), and that for predicting long-term major adverse cardiac event in non–ST-elevated myocardial infarction patients is 0.31 ( 12 ). The cutoff point calculated in this article for predicting arterial stiffness is at a low level in the current study to predict various clinical events.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the count of cells, the ratios between them, such as neutrophil-to-lymphocyte ratio (NLR) ( 7 ), monocyte-to-lymphocyte ratio (MLR) ( 8 ), and platelet-to-lymphocyte ratio (PLR) ( 9 ), are also considered to reflect the inflammation degree. Verdoia et al ( 10 ) found that in people receiving coronary angiography, NLR was independently related to the prevalence and severity of coronary heart disease, and PLR ( 11 ) had a similar effect too; MLR could be an independent predictor of the severity of carotid artery stenosis in patients with ischemic stroke, and it can effectively reflect the severity of coronary artery disease better than NLR ( 12 , 13 ), which diseases are serious adverse events of arterial stiffness. Therefore, we hypothesized that leukocyte counts, platelet counts, and their ratios as indicators of inflammation might be related to arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 For example, the higher MLR value of ischemic stroke patients is related to the degree of carotid artery stenosis and it is an independent risk factor for carotid artery stenosis. 19 It is also associated with stroke-related pneumonia (SAP), which is helpful for clinicians to establish an early diagnosis for patients with high-risk SAP. 20 Moreover, studies have found MLR values to be elevated in patients with affective disorders or schizophrenia.…”
Section: Introductionmentioning
confidence: 99%